2008
DOI: 10.4161/auto.6246
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of autophagy suppresses the intracellular survival ofBurkholderia pseudomalleiin mammalian cell lines

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis, a tropical infection of humans and other animals. The bacterium is an intracellular pathogen that can escape from endosomes into the host cytoplasm, where it replicates and infects adjacent cells. We investigated the role played by autophagy in the intracellular survival of B. pseudomallei in phagocytic and non-phagocytic cell lines. Autophagy was induced in response to B. pseudomallei invasion of murine macrophage (RAW 264.7) cells and a proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(152 citation statements)
references
References 50 publications
9
143
0
Order By: Relevance
“…19 Consistent with the previous study, 12 there was an increase at 2 h and 4 h p.i. in the ratio of MAP1LC3B-II to ACTB and a degradation of SQSTM1 with B. pseudomallei infection as compared to uninfected controls in A549 cells ( Fig.…”
Section: Autophagy Is Inhibited In Response To B Pseudomallei Infectionsupporting
confidence: 81%
See 2 more Smart Citations
“…19 Consistent with the previous study, 12 there was an increase at 2 h and 4 h p.i. in the ratio of MAP1LC3B-II to ACTB and a degradation of SQSTM1 with B. pseudomallei infection as compared to uninfected controls in A549 cells ( Fig.…”
Section: Autophagy Is Inhibited In Response To B Pseudomallei Infectionsupporting
confidence: 81%
“…Previous studies have reported that autophagic evasion of B. pseudomallei is an active process relying on TTSS effector, BopA, which shows 23% amino acid identity to the Shigella TTSS effector, IcsB. 12,22 In Shigella, IcsB competitively binds to its surface protein VirG to inhibit the autophagic process; ATG5 recognizes VirG. 8 Therefore, in a manner analogous to IcsB, it appears unlikely that BopA is the key factor to interfere with ATG10 expression upon B. pseudomallei infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, inflammatory CASP1 has been described to coordinate autophagy in response to L. pneumophila [24]. However, this is the first report of CASP4 deficiency negatively affecting autophagy in macrophages, which may explain the ability of other autophagy-interacting bacteria to be cleared in the presence of CASP4 [2,8,16]. In contrast, clearance of nonpathogenic E. coli does not depend on CASP1 or CASP4 [16,25].…”
Section: Discussionmentioning
confidence: 99%
“…This bacteria-specific autophagic process, designated xenophagy, promotes bacterial clearance and prevents cellular escape. Bacteria such as Listeria monocytogenes [6,7] or Burkholderia pseudomallei [8], although recognized by members of the autophagic pathway, have developed mechanisms to avoid lysosomal degradation and xenophagy.…”
Section: Introductionmentioning
confidence: 99%